Pengaruh Media Sosial dan Teman Sebaya terhadap Perilaku Konsumtif Mahasiswa - Kadeni , Ninik Srijani (Universitas PGRI Madiun, 2018)
The purpose of this study are: 1) to determine the influence of social media on student consumptive behavior; 2) to know the influence of peers against student consumptive behavior; 3) to know the influence of social media and peers against the behavior of consumer consumptive STKIP PGRI Blitar. Type of correlational research with a sample of 95. Data collection techniques using questionnaires and documentation. Data analysis techniques use multiple linear regression. The results showed 1) there is a social media influence on student consumptive behavior; 2) there is influence of association of peer to student consumptive behavior and 3) there is influence of social media and peer to student's consumptive behavior.